Técnicas de conservação pós-colheita para o manjericão - Teixeira, D. A. [UNESP]; Gomes, J. A.O. [UNESP]; Bonfim, F. P.G. [UNESP]; Pardo, P. I.; Mayobre, M. T. (FapUNIFESP (SciELO), 2016)
The study aimed to evaluate which post-harvest technique provided better quality and life of basil branches The experiment was conducted on Medicinal Plants Laboratory of the Department of Horticulture, da Universidade Estadual Júlio de Mesquita Filho, Botucatu, São Paulo. The design was completely randomized with four treatments and six repetitions. The treatments consisted of post-harvest preservation techniques: Control (without post-harvest treatment), plastic packaging, hydrocooling, hydrocooling + package. The variables analyzed were mass loss and lifespan. Data were subjected to analysis of variance and means compared by Tukey test at 5% probability, the ASSISTAT 7.7 beta program. From these data, it was concluded that the use of plastic packaging associated with hydrocooling contributed method for post-harvest storage lifespan and basil.
Postharvest conservation techniques for Basil
Keywords: Lifespan; Packaging; Storage